TCBH Duncan Tanner Essay Prize Winner 2018 Financing the Information Age: London TeleCity, the legacy of IT-82, and the selling of British Telecom - Ward, J (Oxford University Press, 2019)
This article is a history of the privatization of British Telecom. BT's privatization occupies a central position in histories of Thatcherism as a pivotal moment in Thatcherism's ideological focus on popular capitalism. These histories, however, overlook the important intersection of financial institutions and information technology policy in shaping BT's privatization. Financial institutions in the City of London formed a lobbying group, the City Telecommunications Committee, that pressured for BT's privatization and secured preferential treatment for the City from BT, ending a decades-long policy of uniform telecommunications services across Britain. Margaret Thatcher's government positioned BT's privatization as central to the success of two of Britain's information industries, electronics manufacturing and the City of London. Her government also cast BT's privatization as essential to an ‘information revolution’ that, through personal, networked computing, would further personal freedom and free markets. BT's privatization thus performed two important and related functions. First, it oriented Britain's telecommunications network to the City of London's needs, and secondly, it enacted an ‘information revolution’ that was portrayed as essential to the success of the City of London and British electronics. I label this fusion of City finance, neoliberal politics, and British telecommunications the ‘London ideology’, and this ideology shaped the broadly-held assumption that privatizing telecommunications was essential to reaching the ‘information age’.